Design and implementation of two-phase matrix converter - Deniz, Erkan; Aydogmus, Omur (Gazi Univ, Fac Engineering Architecture, 2017)
In this work, a matrix converter has been designed fed by single-phase for speed control of single/two-phase ac motors. This converter can achieve converting directly from single-phase to two-phase. In addition, a new switching algorithm has been proposed to perform ac-ac converting. The proposed Matrix converter can be directly connected between grid and load without using rectifier and dc-link capacitors. Designed converter has been tested for two-phase RL load. The simulation and experimental results of the converter's output voltage and load current are analyzed with the harmonic contents.
Iki-fazli matris çeviricinin tasarimi ve gerçekleştirilmesi
Keywords: Two-phase matrix converter; two-phase motor; energy efficiency; cadSoft EAGLE professional